The Importance of Tourism Infrastructure in Increasing Domestic and International Tourism - Apriyanti, Masayu Endang; Sumaryoto; Meirinaldi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Indonesia is one of the countries that has the main capital in the tourism sector, namely abundant natural resources that are enchanting, however, it would be a shame if it is not managed well, because the huge potential that exists will be wasted and cannot be utilized for the welfare of the community. Apart from natural wealth, the success of a tourism sector is influenced by other factors, such as cultural diversity, traditions and local wisdom, including support from the availability of existing infrastructure, as an attraction that encourages tourists to visit, then supports the development and progress of tourism, which encourages increasing regional income around tourist attractions and contributing greatly to the national economy. In order for the tourism sector to be able to be competitive and highly attractive, apart from having an appropriate and effective strategy, it must also be able to provide adequate infrastructure in all tourism objects, because these facilities are the main gateway in providing the best service for tourists and function as a supporter that provides various conveniences for tourists to reach the desired tourist destinations, provides comfort and guarantees their safety while traveling, all of which will increase the ability of the tourism industry to continue to strive to contribute optimally in increasing economic growth, through the utilization of natural resource wealth. , the variety of cultures and local wisdom that exist. This research focuses on the importance of the availability of tourism infrastructure in increasing tourist visits in domestic tourism and international tourism.